Gestos de autoria em dissertações: uma análise dialógico-discursiva. - Barbosa, Ângela Alves de Araújo (2023)
Our doctoral dissertation is based on the Dialogic Theory, which conceives language as its dialogical nature and the genres of discourse more than particular modes of discursive communication, but also as modes of relation and world understanding indissociable from the element of authorship. The voice of the young researcher, in academic scientific texts of the Humanities, has been pointed out by discursive and textual studies to tend towards erasure, which adds to our research problem of the constitution of the voice of the master's researcher in written texts of the section of theoretical foundation of the genre of the dissertation. Our thesis is that the authors of the research inscribe their voices in the theoretical foundations in variability of modes, in different gestures of authorship. With the general objective of investigating how the gestures of authorship are given in the theoretical foundation of master's dissertations, the specific objectives are outlined in the sense of: (i) identifying the voices introduced and the points of view in the theoretical foundation of master's dissertation; (ii) analyzing the dialogical discursive movements in the theoretical foundation, which are movements of senses. The methodology is qualitative through the procedure of Dialogic Discourse Analysis, which does not propose a predetermined, fixed and replicable method, but rather an active and flexible analysis, which outlines a unique style of each dialogic analyst. The corpus of our research is composed of texts from theoretical foundations of two master's dissertations in the public domain, available in the digital repository of theses and dissertations of Capes (Catalogue of Theses and Dissertations). Both dissertations are from the field of knowledge of language studies and based on the dialogic theory, being one dissertation in the research line "Structure, Organization and discursive and textual functioning" and one dissertation in the research line "Multiliteracy, Discourses, Processes of Production of Meaning", coded in the analysis as DM1 and DM2. In this way, we seek to safeguard the identification of the authors of the dissertations as an ethical act in the activity of our research. Based on Bakhtinian concepts, our analysis mobilizes the following categories: voices, point of view, valuation and dialogical relationship. The data point to a triangulation of the author's vision (subject, society and culture) in the theoretical frameworks of both dissertations, and to the constitution of different gestures of authorship.